Oh, yuck! : the encyclopedia of everything nasty - Masoff, Joy, 1951-; Sirrell, Terry (New York : scholastic, 2000)
An alphabetical collection of articles about disgusting things, from acne, ants, and bacteria to worms, x-periments, and zits.
Includes bibliographical references (p. 203-204) and index.
G6
Keywords: Handbooks, vade-mecums, etc. -- Juvenile literature; Aversion -- Miscellaneous -- Encyclopedias, Juvenile; Aversion -- Encyclopedias, Juvenile; Curiosities and wonders